2019
DOI: 10.3389/fped.2019.00425
|View full text |Cite
|
Sign up to set email alerts
|

Education, Altitude, and Humidity Can Interactively Explain Spatial Discrepancy and Predict Short Stature in 213,795 Chinese School Children

Abstract: Backgrounds and Objectives: The north–south height distinctions in Chinese children suggest that some geographical–climatic factors could determine height variation of short stature. In a national health survey, we aimed to explore the spatial distribution of short stature on city scales, and detect its socio-economic and geographical–climatic factors.Methods: Data on the prevalence of short stature were obtained from a 2014 cross-sectional survey of China (CNSSCH). In total, 213,795 Han Chinese students aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(52 reference statements)
0
3
0
Order By: Relevance
“… 10 The age-standardized prevalence of short stature is 3.70% in China. 11 A number of studies have found that short stature may affect the physical and mental health of children, especially boys. 12 Bone development is regulated by growth hormone, thyroid hormone, and estrogen.…”
Section: Introductionmentioning
confidence: 99%
“… 10 The age-standardized prevalence of short stature is 3.70% in China. 11 A number of studies have found that short stature may affect the physical and mental health of children, especially boys. 12 Bone development is regulated by growth hormone, thyroid hormone, and estrogen.…”
Section: Introductionmentioning
confidence: 99%
“…We recognize the fact that environmental altitude and humidity may contribute to a child's growth and adult height. In Nepal and Peru, at the bottom of height spectrum, the influence of low oxygen pressure at high altitude has strong effect on growth along with the socio-economic environment (21). The statistical approach for analysis is to analyze all factors one by one.…”
Section: Discussionmentioning
confidence: 99%
“…The short stature and small body size of cattle observed in the Ethiopian high-altitude cattle confer the evidence. Though confirmatory analysis is required to differentiate the nature of short stature and small body size for HA adaptation in Ethiopian cattle, it could be a possible mechanism of the cold and high-altitude adaptation as it was reported in humans adapted to high altitude (Ma et al, 2019).…”
Section: Novel Candidate Gene Identified In This Studymentioning
confidence: 95%